Negara, BUMN dan Peranan Hukum Dalam Pembangunan Ekonomi: Refleksi Seorang Advokat - Teuku Syahrul Ansari (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2018)
In developing the Business Judgment System for State-Owned Enterprises (Persero) in Indonesian Economic Law, it is necessary to elaborate on the theory of the role of law in economic development. According to J.D. Mrs. Hart has three elements that must be developed in the legal system so that the law plays a role in economic development, namely predictability (stability), stability (stabilitiy), justice (fairness). The role of the law, basically refers to the main purpose of the law, which is to create an orderly society. Order and balance in society need to be achieved, so that human interests will be protected in achieving their goals. In general, the law functions to divide rights and obligations, regulate how to solve legal problems and maintain legal certainty.